FAKTOR-FAKTOR YANG DAPAT MEMPENGARUHI PENGELOLAAN KEUANGAN DESA KECAMATAN SIULAK MUKAI KABUPATEN KERINCI - Rio Baviga (UNIVERSITAS KARIMUN, 2023)
This study aims to determine the factors: (1) Competence of village financial management apparatus, (2) community participation, (3) village government organizational commitment (4) compliance with financial reports. This research is classified as an ex post facto, causal associative, and quantitative approach. The population in this study were all villages in the Siulakmukai sub- district, Kerinci district which consisted of 14 villages. The sampling technique used purposive sampling. The number of respondents was 42 people who had met the criteria and the data analysis tool used multiple linear regression. The results of this study indicate that the competence of village financial management officers (X1) partially has a negative effect on village financial management, as evidenced by tcount > ttable (-0.192 > -2.02619) and with a significance value = 0.849 > 0.05. Meanwhile, community participation ( X2) has a positive effect on village financial management as evidenced by tcount > ttable (27.329 > 0.02619) and with a significance value = 0.000 <0.05. Meanwhile, village government organizational commitment (X3) has a negative effect on financial management, this is evidenced by tcount > t table (-0.655 > -2.02618) and with a significance value = 0.516 > 0.05. Meanwhile, obedience to financial statements (X4) has a significant positive effect on village financial management, as evidenced by tcount < ttable (0.591 > 2.02619) and the significance value = 0.558 > 0.05. Competence of village financial management apparatus (X1), Community participation (X2), Meanwhile, village government organizational commitment (X3), Compliance with financial reports (X4) simultaneously have a significant positive effect on village financial management, this is evidenced by Fcount > Ftable (196,236 > 2, 62) and with a significant value = 0.000 <0.05.